Simulation Method for Complex Constraints and the Necessity of Joints in an Early-Age, Large-Volume Concrete Slab—A Case Study of Complex Column Grids and Wall Constraints - Wenqian Li; Wei Jiang; Chen Fu; Zhiyi Li; Hao Zhang (Buildings)
In modern engineering and construction, mass concrete structures impose stringent requirements on crack control. However, there exists a conflict between design and construction: design primarily addresses the structural performance needs during service phases, while construction must confront the challenges of early-stage performance. It is, therefore, essential to investigate the complex constraints affecting mass concrete structures during their early stages. In this paper, a spring foundation was employed to simulate the intricate constraints on mass concrete footings at early ages, with parametric analyses systematically exploring the influence of spring constant values. The study reveals that excessively large spring constants overestimate constraint effects, leading to amplified stress calculations, while overly small constants underestimate actual constraints, resulting in diminished computed stresses. Building on these findings, this work establishes a quantitative relationship between spring constants and stress responses. Notably, a spring constant table incorporating various constraint scenarios was compiled to provide engineering recommendations. The goal was to reconcile the conflict between early-age and in-service performance through precise constraint modeling, offering theoretical foundations for selecting rational constraint parameters. This approach resolves critical issues in bottom slab design optimization and construction control, particularly addressing abnormal stress distributions and crack control challenges stemming from complex constraints.